FAKTOR YANG MEMPENGARUHI MINAT NASABAH GADAI SYARIAH DENGAN GADAI KONVENSIONAL PADA PT. PEGADAIAN Tbk. Kota Mataram - Maulana Ibrahim; Triana Lidona Aprilani (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2022)
This study aims to determine the factors that influence the interest of customers of PT Pegadaian Syariah BTN Sweta branch with PT Pegadaian conventional Selaparang branch in terms of service quality factors, location factors and promotion factors This research was conducted at PT Pegadaian Syariah BTN Sweta branch and PT Pegadaian conventional Selaparang branch with the type of case study research, the method used in this study was qualitative. Methods of data collection is done in three ways, namely observation, interviews, and documentation. Data collection is carried out to obtain data in the data field. Based on the results of the study, it can be concluded that the factors that influence customer interest are the similarities and differences between PT. Sharia pawnshop BTN Sweta branch with PT. Conventional Pegadaian Selaparang branch, which is located on the service quality factor that most dominantly affects customer interest in making a pawn, then followed by the location factor where customers who have a place close to the pawnshop to make a pawn are very profitable for customers because it is close to making it easier for the customer to manage the necessary files. While the condition of living quite far is actually not an obstacle and does not become a benchmark for a place to pawn because there is a need so that customers will bring in pawns wherever they are. While the difference is PT. Sharia pawnshop BTN Sweta branch with PT. The Selaparang branch of Conventional Pawnshops lies in the promotion factor. At the sharia pawnshop branch of BTN Sweta, customers are very interested in promotions such as: providing low interest, the cost is calculated from the value of the goods, has the principle of trust and provides loans in accordance with Islamic sharia. Meanwhile, customers at the Selaparang conventional pawnshop are interested in promotions such as easy requirements, fast disbursement of funds, compensation for pawned goods, gold savings products and longer interest rates. From the results of this analysis, it is suggested that PT. Sharia pawnshop BTN Sweta branch with PT. Selaparang branch conventional pawnshops to improve management performance and provide even better services, provide comfortable and safe facilities and increase socialization and promotion of how to pawn the sharia pawnshops in BTN Sweta branch and conventional pawnshops in Selaparang branch. Thus, customers better understand the concept and products of pawnshops.